South-to-North Water Diversion stabilizing Beijing’s groundwater levels - Long, Di; Yang, Wenting; Scanlon, Bridget R.; Zhao, Jianshi; Liu, Dagen; Burek, Peter; Pan, Yun; You, Liangzhi; Wada, Yoshihide (Nature communications, 2020)
Groundwater (GW) overexploitation is a critical issue in North China with large GW level declines resulting in urban water scarcity, unsustainable agricultural production, and adverse ecological impacts. One approach to addressing GW depletion was to transport water from the humid south. However, impacts of water diversion on GW remained largely unknown. Here, we show impacts of the central South-to-North Water Diversion on GW storage recovery in Beijing within the context of climate variability and other policies. Water diverted to Beijing reduces cumulative GW depletion by ~3.6 km 3 , accounting for 40% of total GW storage recovery during 2006–2018. Increased precipitation contributes similar volumes to GW storage recovery of ~2.7 km 3 (30%) along with policies on reduced irrigation (~2.8 km 3 , 30%). This recovery is projected to continue in the coming decade. Engineering approaches, such as water diversions, will increasingly be required to move towards sustainable water management. The authors here address water sustainability in the greater area of Beijing, China. Specifically, the positive effects towards Beijing groundwater levels via water diversion from the Yangtze River to the North are shown.